2017
DOI: 10.18203/2394-6040.ijcmph20170255
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of gestational hypertension among pregnant women (2006-2015) in Enugu State, Southeast Nigeria: a retrospective study

Abstract: INTRODUCTIONGestational hypertension (GHTN), formerly known as pregnancy induced hypertension, is defined as a new rise in blood pressure (BP) ≥140/90mm Hg, presenting at or after 20 weeks gestation without significant proteinuria (≥ 300mg/24 hour urine collection of urine, or 2 specimens of urine collected ≥ 4 hours apart with ≥ 2+ on the protein reagent strip, or protein creatinine ratio (PCR) ˃ 30mg/mmol) or other features of preeclampsia which usually resolves within 6-12 weeks of delivery.1,2 It is the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In this study, majority of cases admitted with PIH were primigravida (65%). In a retrospective study conducted in southeast Nigeria by Umegbolu EI et al, the incidence of PIH was higher among nulliparous women (7.7%) as compared to (5.5%) in multiparous women [18] . In a study by Shikha Saxena et al also the majority of cases were primigravida (57%) [15] .…”
Section: Discussionmentioning
confidence: 91%
“…In this study, majority of cases admitted with PIH were primigravida (65%). In a retrospective study conducted in southeast Nigeria by Umegbolu EI et al, the incidence of PIH was higher among nulliparous women (7.7%) as compared to (5.5%) in multiparous women [18] . In a study by Shikha Saxena et al also the majority of cases were primigravida (57%) [15] .…”
Section: Discussionmentioning
confidence: 91%
“…This is consistent with the results of our study. Umegbolu and Ogamba ( 42 ) reported that first pregnancy is a risk factor for PIH and its occurrence is more common in nulliparous than multiparous women. Howell ( 43 ) showed that in women with prior cesarean delivery, PIH was significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…GH was defined as a blood pressure of ≥140/90mmHg with no proteinuria. 23 Late-onset PE was defined as a sustained blood pressure of ≥140/90 mmHg with proteinuria of at least 300 mg after 34 weeks of pregnancy. 1 …”
Section: Methodsmentioning
confidence: 99%